REVOLUTIONIZING RELIGIOUS EDUCATION: THE ROLE OF MOBILE GAMES IN TEACHING HADITH TO EARLY LEARNERS - Nurul Fathihin Mohd Noor Shah; Mohamad Hafizuddin Mohamed Najid, (International Prophetic Conference (SWAN) FPQS USIM, 2024)
The increasing integration of mobile devices into daily life has led to a greater recognition of their educational potential, particularly among younger learners. This paper explores integrating mobile game-based learning into a Hadith education curriculum, exclusively designed for children between the ages of 4 and 6 years old. The study aims to exploit the captivating potential of mobile games to facilitate the dissemination of Hadith teachings in a way that appeals to the technologically savvy generation. By integrating gamification elements into the learning environment, the proposed mobile application aims to establish an engaging and fun learning environment that captivates children's attention and improves their comprehension and memory of Hadith. This approach is based on current instructional methods that promote interactive and learner-centered learning experiences. The research highlights the importance of mobile games as a significant educational tool, with the potential to revolutionise conventional learning methods and contribute to the wider discussion on technology-enhanced education. The purpose of this study is to demonstrate how the deliberate incorporation of technology can enhance the educational environment, thereby increasing the accessibility and enjoyment of religious studies for young students.